2016
DOI: 10.1177/0379572115624289
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perceptions and Views About Breastfeeding Practices Among Emirati Mothers

Abstract: Background: Understanding women's breastfeeding perceptions and experiences is increasingly recognized as a vital tool to provide effective support that would encourage the extension of the breastfeeding period. Objective: To identify and explore the perceptions and views that influence the feeding and weaning decisions of Emirati mother. Methods: A qualitative study using indepth interviews was undertaken with a convenience sample of 45 Emirati mothers who had infants aged between 6 months and 2 years. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 41 publications
(48 reference statements)
4
23
0
9
Order By: Relevance
“…It is interesting to note that many mothers referred to their families as a source of breastfeeding information, similar to what has been reported from other countries in the region [27,28]. Cues that a mother receives from her family and friends become her main source of information when back home after delivery.…”
Section: Plos Onesupporting
confidence: 71%
See 1 more Smart Citation
“…It is interesting to note that many mothers referred to their families as a source of breastfeeding information, similar to what has been reported from other countries in the region [27,28]. Cues that a mother receives from her family and friends become her main source of information when back home after delivery.…”
Section: Plos Onesupporting
confidence: 71%
“…Cues that a mother receives from her family and friends become her main source of information when back home after delivery. Thus familial support is essential for mothers as the social norms dictated by the woman's family may influence her breastfeeding habits [14,27,28]. Since the majority of participants would like to communicate with a lactation consultant soon after giving birth, having lactation consultants in hospitals for breastfeeding support is crucial to the establishment and continuation of breastfeeding.…”
Section: Plos Onementioning
confidence: 99%
“…Timely initiation of breastfeeding is the provision of a mother's breast milk to infants within 1 h of birth [1]. The practice of early initiation helps the child get colostrum, which contains antibodies that help protect the infant from common childhood illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because health professionals are considered to be the most knowledgeable with respect to infant care practices. On the Contrary, in Emirati and Asella Town, southeast Ethiopia, the respondents recognized their own mothers, the child's father, a close relative, friend, or neighbor as the source of information with the greatest impact on maternal BF decision (Radwan & Sapsford, 2016;Sasie et al, 2017). Mothers in the Okola Health District, Cameroon, also acknowledged family members, friends, and neighbors as the source of information with the greatest impact on their BF decision (Ngameni et al, 2011).…”
Section: Effects Of Sources Of Bf Information On Maternal Decisionmentioning
confidence: 99%
“…From investigations on low-income black Americans, it was found that while one-to-one educational programs were most effective in increasing initiation for women who intended to bottle feed, group programs had more impact on initiation for women who planned to breastfeed (Health Development Agency, 2003). On the contrary, it was realized that in the United States and Emirati, the family has the greatest impact on the mother's BF decision (Odom, Li, F I G U R E 4 Frequency of BF Scanlon, Perrine, & Grummer-Strawn, 2014; Radwan & Sapsford, 2016). Also, De Oliveira, Camacho, and Tedstone (2001) indicated that the effectiveness of interventions to increase duration of any BF on maternal decision did not depend on whether they were given by health professionals or by peer counselors.…”
Section: Effects Of Sources Of Bf Information On Maternal Decisionmentioning
confidence: 99%